Subjective memory complaints, perceived stress and coping strategies in young adults - Molina-Rodriguez, Sergio; Pellicer-Porcar, Olga; Mirete-Fructuoso, Marcos; Martinez-Amoros, Estefanía (Revista de neurologiá, 2016)
Subjective memory complaints are becoming more and more frequent among young adults. There are currently no studies in the literature that analyse the relation among memory complaints, perceived stress and coping strategies as a whole in young adults. To determine the contribution made by perceived stress and different coping strategies on subjective memory complaints in healthy young adults. The sample consisted of 299 university students, of whom 71.6% were women, with a mean age of 22.54 ± 4.73 years. The variable 'memory complaints' was measured with the memory failures questionnaire; the variable 'perceived stress' was measured with the perceived stress scale, and the variables referring to coping strategies were measured using the coping strategies inventory. The variables that made a higher contribution to the variance of the memory complaints are, first, perceived stress and positive problem-focused coping strategies, and, second, negative coping strategies focused on the emotion and on the problem. The positive emotion-focused coping strategies do not make any contribution. Again we find evidence of the influence of stress on memory processes. The use of positive problem-focused coping strategies, such as cognitive restructuring and problem-solving, can be beneficial to lessen the presence of memory complaints. Further research on this matter is warranted.